The reformation of Muslim education In Malaysia: ensuring relevance and overcoming challenges - Hashim, Rosnani (2014)
Education in the Muslim World is at a crossroad – to decide whether to continue the inherited secular education system left by the colonial master; or to fall back on the conservative, traditional religious education system that has survived despite the secular onslaught; or to find a new system that can accommodate both. In the context of Malaysia, before the beginning of Western colonialism there already existed the non-formal Qur’anic schools and pondok. The English colonized Malaya in the 18th century until Independence in 1957. By the time they left, the education for the Muslims became divided into three categories: traditional pondok and madrasah education, Malay vernacular schools, and the English schools. The latter two categories offer secular education with nothing on religion was taught. The English schools had more racial diversity in contrast to the Malay national or the religious schools which was basically catering to the Malays. The first category of schools was left on its own as private community institutions. Later, in 1970, the government gradually converted both the Malay vernacular and the English schools, that is, the second and third category, into national schools having Malay language as its medium of instruction. These two systems continued to grow, producing Muslims who were in many instances at conflict with one another due to the conflicting worldviews preached in the school systems. How has Muslim education developed since then, in particular Islamic religious education? Is the development healthy for the ummah’s relevance in the contemporary world? Does it achieve the aims of Islamic Education? What are some of the issues and challenges it has to overcome? These are the questions that will guide this paper.